PEMANFAATAN PEMBAYARAN ONLINE BAGI E-COMMERCE USAHA KECIL DAN MENENGAH - Sugiharto Sugiharto; Abdullah Umar; Agung Hari Sasongko; Glory Aguzman (BBM (Buletin Bisnis & Manajemen), 2019)
Today, technology has entered into all business fields where the digital era is very helpfuland facilitates business both in terms of marketing, sales and distribution. The utilizationof these technologies will directly increase sales volume and the potential for anincreasingly large market. This will be very beneficial for medium and small businesses,where they still use a lot of conventional methods and have not used the technology sideand have not yet entered e-commerce. Expansion of the market or market is the mostimportant thing in the business world so that through E-Commerce, market coverage isno longer only in the area where the MSMEs are located but is widespread throughoutthe world wherever it can be accessed. In addition to the wider market, it can also accessreal-time payments that will facilitate the payment process directly by consumers andcan make the flow of cash out of the business more controlled which is no longer anobstacle. This online payment system is not always related to e-Commerce, but also withdirect transaction activities at the place of business can also be done so that cashless andalso in the online payment there will be a sales transaction report that will make therecording directly available in the payment system online. This benefit is very helpful forsmall and medium businesses that are expected to increase their sales growth and theirfinancial management will be helped.